Potential of RNA interference in the study and management of the whitefly, Bemisia tabaci. Issue 2 (28th November 2018) - Grover, Sajjan; Jindal, Vikas; Banta, Geetika; Taning, Clauvis Nji Tizi; Smagghe, Guy; Christiaens, Olivier
Abstract: Whiteflies cause considerable losses to crops, directly by feeding, and indirectly by transmission of viruses. The current control methods consist of a combination of different control tactics, mainly still relying on unsafe and non‐ecofriendly chemical control. RNA interference (RNAi) is a post‐transcriptional gene‐silencing strategy in which double‐stranded RNA (dsRNA), corresponding specifically to a target gene, is introduced in a target organism. Research on RNAi in the previous decade has shown its success as a potential insect control strategy, which can be highly species‐specific and environment friendly. In whiteflies, the success of dsRNA delivery through the oral route opened possibilities for its management through plant‐mediated RNAi. To date, several genes have been targeted in whiteflies through RNAi and these assays demonstrated its potential to manage whiteflies at lab level. However, further research and investments are needed to move toward an application at field level. In this review, for the first time, we collected the literature on genes targeted for silencing via RNAi in whiteflies and discuss the potential of RNAi in whitefly pest control. We also discuss likely delivery methods, including transgenic in planta delivery and symbiont‐mediated delivery, and its potential for studying and interfering with insecticide resistance mechanisms and virus transmission by whiteflies. Abstract :